Assertivity Review from Self-Concept and Emotion Regulation in Student of The Faculty of Psychology, Prima Indonesia University - Hartini, Sri; Prasetio, Veronica; Jonathan, Willie; Marbun, Chris Alfiany; Annike, Annike (Budapest International Research and Critics University, 2021)
The purpose of this study was to examine and determine the effect of self-concept and emotion regulation on assertiveness. The sample of this study amounted to 198 students from the Faculty of Psychology, University of Prima Indonesia with the method of proportionate stratified random sampling. Collecting data in this study used an assertiveness scale consisting of 25 items, a self-concept scale consisting of 24 items, and an emotional regulation scale consisting of 23 items. The results of this study indicate that there is an influence between self-concept and emotional regulation on assertiveness with the test value of F = 45,153 and sig = 0,000. The results showed that there was a positive influence between self-concept and assertiveness which was supported by the beta coefficient value of 0,446 and sig. 0,000 (p < 0,01), and there is a positive influence between emotion regulation on assertiveness with a beta coefficient of 0,196 and sig. 0,004 (p < 0,01). The research data were analyzed using the correlation method of multiple linear regression analysis. The results showed that the effective contribution given by self-concept and emotional regulation to assertiveness was 31 percent and the remaining 69 percent was influenced by other factors not examined.